BREAKING DOWN WORDS: A STRUCTURAL ANALYSIS OF STUDENTS’ WRITTEN OUTPUTS - TAMAYO, RIA (International Journal of Arts, Sciences and Education, 2022)
The study structurally analyzed the written outputs of the students which were submitted online. The analyzed outputs were lifted from portion of the submitted academic requirements, quizzes, compositions and essays of the students. The evident errors committed by the respondents were classified according to the types of error. The findings of the study revealed that the university students have committed syntactical and structural errors which were reflected in their written outputs. The evident and common errors committed by the respondents were misplaced and dangling modifiers, wrong verb usage, lack of parallel structure, subject-verb agreement, run-on sentence, misspelled words, wrong word usage, referent not specified, redundant, fragment, repetitive words, wrong subject-pronoun used and fragmented sentences. This finding implies that even if the respondents are already second year college, they still have not mastered the rules in grammar and have not fully acquired the academic writing skills and competencies. This further implies that the students have weak foundation in terms of grammar usage. Their outputs are not syntactically and structurally bounded with the standard on writing composition. This paper has academic inferences to language teaching and learning.